A review on the integrated Islam and science teaching model in Malaysia - Zaim Zamri,; Norshariani Abd Rahman,; Wan Nasyrudin Wan Abdullah,; Zetty Nurzuliana Rashed,; Norfariza Mohd Radzi,; Ab Halim Tamuri,; Ahmad Ashrif A Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A review of the integration models between science and Islam needs to be studied to see the fundamental aspects that are important in constructing an integrated Islam and science teaching model to face the IR 4.0 era. Four models have been reviewed: the Tawhidic Science Model, the Muslim Scientist Model, the Integrated Constructivism Model, and the Ulul Albab Model. Three aspects will be reviewed from the four models which are: 1) aim for the construction of models 2) source of knowledge and 3) cognitive aspects involved. This research uses a qualitative method of analyzing library material. The findings show that all four models aim to uphold God’s belief through scientific learning and al-Qur’an is considered as the source of knowledge for all four models. This study also has identified the key cognitive aspects required for an educational approach that integrates science and Islam, which are tadabbur (contemplation), ibrah(lesson), and reflection, in addition to other conventional cognitive aspects, such as innovating and creative thinking. These characteristics can be suggested to produce a comprehensive integrated Islam and science curriculum taxonomy which is important for the holistic development of human beings in this new era